The therapeutic perspective of relapsed/refractory Waldenström Macroglobulinemia: what comes next? - Danesin, Nicolò; Leone, Giovanni; D’Antiga, Mattia; Carraro, Marco; Scapinello, Greta; Trentin, Livio; Piazza, Francesco (Frontiers in Hematology, 2025)
Waldenström Macroglobulinemia (WM) is a rare, indolent B-cell lymphoma that primarily affects elderly individuals. Although frontline chemoimmunotherapy and Bruton’s tyrosine kinase inhibitors (BTKi) can provide durable responses, most patients eventually relapse, posing ongoing clinical challenges. This review outlines the current therapeutic landscape for relapsed and refractory (R/R) WM, with a focus on emerging treatment strategies. While the efficacy of chemoimmunotherapy and targeted agents in the frontline setting is well established, the management of relapsed disease largely relies on early-phase clinical trials, often involving heterogeneous populations. Covalent BTKi (cBTKi), including ibrutinib, zanubrutinib, and acalabrutinib, remain the cornerstone of R/R WM therapy, with varying safety and efficacy profiles. Resistance to cBTKi, frequently associated with the BTK C481 mutation, confers poor survival outcomes. The development of non-covalent BTKi (ncBTKi) and BTK degraders as promising alternatives. In this setting, the molecular profile-particularly mutations in MYD88, CXCR4, and TP53-plays a pivotal role in predicting treatment response and prognosis. BCL-2 inhibitors, such as venetoclax, are also under investigation. A phase II trial of venetoclax monotherapy demonstrated encouraging response rates in heavily pretreated patients, underscoring its potential in BTKi-resistant or intolerant cases. Additional novel therapies under evaluation include proteasome inhibitors, PI3K inhibitors, and immunotherapeutic approaches like CAR-T cells and bispecific antibodies. While early results are promising, larger studies are needed to validate these strategies. In addition, consolidation or salvage with hematopoietic stem cell transplantation could be considered in young heavily pretreated patients, especially in the context of BTKi refractoriness. It is therefore important to underline that given the chronic, relapsing course of WM, personalized treatment sequencing-accounting for comorbidities and prior therapies-is essential for optimizing outcomes. In conclusion, although significant advancements have been made in the management of R/R WM, continued research through randomized trials and biomarker-driven approaches is critical for refining the treatment strategies and improving long-term survival in this challenging disease.